Structural evolution during gelation of pea and whey proteins envisaged by time-resolved ultra-small-angle x-ray scattering (USAXS). (May 2022) - Chen, Da; Kuzmenko, Ivan; Ilavsky, Jan; Pinho, Lorena; Campanella, Osvaldo
Abstract: Hydrogels from plant proteins commonly exhibit inferior gel strength compared to those from dairy proteins partially due to their distinct gel networks. How protein aggregates to form such networks in response to heat remains largely unknown. In here, pea (PPI) and whey (WPI) protein isolate gels were produced at the same protein content and similar heating/cooling rate. The process was monitored using rheology, microscopy and in situ ultra-small-angle x-ray scattering (USAXS). Rheology showed an initial decrease in G′ and G″ in PPI followed by a steady increase when the temperature surpassed ∼60 °C whereas a much higher temperature (∼80 °C) was required for WPI, both using 2 °C/min heating rate. Microscopy showed a coarse and heterogenous network in PPI, whereas for WPI, the network was finer and more continuous. In both gels, nano-sized spherical or ellipsoidal particles were present as the basic constituents. USAXS found individual protein was dominant in PPI or WPI solution at temperature below 57 °C. Their proportions decreased together with appearance of aggregates with an average R g of 9–10 nm in PPI and 6–7 nm in WPI at higher temperature. The size of the aggregates changed slightly during further heating and cooling, but their proportions increased. Power law exponents revealed the aggregates were mass fractals for WPI and PPI gels, and they became more compact during heating. Our findings suggested formation of primary aggregates in protein gel networks is a more organized process and provided theoretical guidance for production of high protein food gels with desirable texture. Graphical abstract: Image 1 Highlights: PPI displayed a coarser and more heterogeneous gel network than WPI at pH7. PPI and WPI gel were composed mainly of aggregates of a few protein molecules. The aggregates were formed at temperature ≤68 °C for both PPI and WPI. Sizes of the aggregates were not changed but their amounts increased during cooling. The aggregates were surface fractals for both gels and larger in size in PPI gel.